3 2 + 4 − 2 2 + 3 2 − 4 − 2 2
If x equals the expression above, then find the value of x 3 − 3 2 x + 4 .
This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
Simple standard approach.
Bonus question : What are the other roots to the equation x 3 − 3 2 x − 4 = 0 ?
If we consider the identity ( u + v ) 3 − 3 u v ( u + v ) − ( u 3 + v 3 ) = 0 and make it match with the equation, we get the system:
x = u + v u v = 2 u 3 + v 3 = 4
By Vieta's formulas, the solutions for u and v are:
u , v = 3 2 ± 4 − 2 2 .
But, ( u w , v w 2 ) and ( u w 2 , v w ) are also solutions of the system, where w is a primitive cube root of unity.
So,
x 1 = 3 2 + 4 − 2 2 + 3 2 − 4 − 2 2 x 2 = 3 2 + 4 − 2 2 w + 3 2 − 4 − 2 2 w 2 x 3 = 3 2 + 4 − 2 2 w 2 + 3 2 − 4 − 2 2 w
1.656235178 -0.828117589+0.5561405236i -0.828117589-0.5561405236i
assume x = ( 2 + 4 − 2 2 ) 1 / 3 + ( 2 − 4 − 2 2 ) 1 / 3
x 2 = ( 2 + 4 − 2 2 ) 2 / 3 + ( 2 − 4 − 2 2 ) 2 / 3 + 2 × ( 4 − ( 4 − 2 2 ) ) 1 / 3
taking the last term we find that
( 4 − ( 4 − 2 2 ) ) 1 / 3 = ( 2 2 ) 1 / 3 = 2 1 / 3 × 2 1 / 6 = 2 then
x 2 = ( 2 + 4 − 2 2 ) 2 / 3 + ( 2 − 4 − 2 2 ) 2 / 3 + 2 2
x 2 − 3 2 = ( 2 + 4 − 2 2 ) 2 / 3 + ( 2 − 4 − 2 2 ) 2 / 3 − 2
x × ( x 2 − 3 2 ) = ( 2 + 4 − 2 2 ) + ( 2 − 4 − 2 2 )
x 3 − 3 2 x = 4
x 3 − 3 2 x + 4 = 8
Problem Loading...
Note Loading...
Set Loading...
x = 3 2 + 4 − 2 2 + 3 2 − 4 − 2 2
Cube both sides:
x 3 = 2 + 4 − 2 2 + 3 3 2 + 4 − 2 2 3 2 − 4 − 2 2 ( 3 2 + 4 − 2 2 + 3 2 − 4 − 2 2 ) + 2 − 4 − 2 2
x 3 = 4 + 3 3 ( 2 + 4 − 2 2 ) ( 2 − 4 − 2 2 ) x
x 3 = 4 + 3 3 4 − ( 4 − 2 2 ) x
x 3 = 4 + 3 3 8 x
x 3 = 4 + 3 2 x
x 3 − 3 2 x − 4 = 0
Finally, add 8 to both sides:
x 3 − 3 2 x + 4 = 8